“A gente faz a faculdade... pra criança normal”: representações sociais de educadoras sobre as diferenças - Cristiane Perol da Silva (Nepan editor, 2021)
From two surveys in public early childhood education schools, the social representations of edu-cators around differences in relation to childhood is highlighted. A theoretical-methodological cartographic perspective is assumed that dialogues with the assumptions of the Social Theory Representations. Some challenges stand out for the strengthening of a democratic State of law, since childhood, since the main result of the studies show social representations about some differences as «assumed» by the teachers for a political-pedagogical positioning, while others do not make up the same priority status or within the scope of the school›s social function. It is essential to defend that differences (in their various aspects) should be made visible and debated, in the direction of Education in Human Rights, with a view to expanded social justice and the fullness of childhoods. In this sense, the decolonial pedagogy becomes central to the process of creating counter hegemonies.